Transformation of Mathematics Learning in the Digital Age: Improving Student Understanding with Learning Videos and Educational Game Applications - Yuda Ariyanto, Soni; Adilla, Ulfa; Nurul Hidayah, Novita; Parino, Parino (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research aims to explore the role of digital media, especially learning videos and educational game applications, in improving students' understanding of mathematical concepts at SD Negeri 101/II Bungo. The research method used is a qualitative approach with a case study design. Data was collected through in-depth interviews with teachers and students, as well as direct observation of learning activities involving digital media. Data analysis was carried out using reduction, display, and verification techniques to identify the main themes that emerged from interviews and observations. The results show that digital media, especially learning videos and game applications, can increase student engagement, make it easier for them to understand mathematical concepts, and increase learning motivation. Students who use this media are more active and have a deeper understanding compared to students who use conventional learning methods. The implications of this study show that the use of digital media in mathematics learning can be an effective solution to improve the quality of education, especially in areas with limited resources. The research also provides new insights into the role of technology in primary education, and encourages further development of the use of digital media for more holistic learning.